Measuring Healthcare Services Quality in the Private Hospitals of Dhaka City, Bangladesh: An Empirical Study - Zubayer, Mahmud (British Journal of Marketing Studies, 2017)
The aim of this research is to determine the healthcare services quality in the private hospitals of Dhaka City, Bangladesh. The research attempted to detect the key variables that can be employed to determine the current standard of the healthcare service quality from the patient’s point-of-view. The study has selected 221 respondents by the convenience sampling technique and the multivariate analysis technique like “factor analysis” was employed to identify the factors. The results from the analysis has shown that, knowledgeable & hygienic, language & cleanliness, degrees & equipment, tests & meals, needs & caring, attractive & punctual,  examination & skills,  admission process and  professionally dressed have emerged important factors for determining the quality of the private healthcare services.